2013
DOI: 10.1371/journal.pone.0053696
|View full text |Cite
|
Sign up to set email alerts
|

Stagnant Neonatal Mortality and Persistent Health Inequality in Middle-Income Countries: A Case Study of the Philippines

Abstract: BackgroundThe probability of survival through childhood continues to be unequal in middle-income countries. This study uses data from the Philippines to assess trends in the prevalence and distribution of child mortality and to evaluate the country’s socioeconomic-related child health inequality.MethodologyUsing data from four Demographic and Health Surveys we estimated levels and trends of neonatal, infant, and under-five mortality from 1990 to 2007. Mortality estimates at national and subnational levels were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 45 publications
4
33
3
1
Order By: Relevance
“…The Countdown to 2015 Equity Analysis Group has resulted in several equity trend analyses of countries in changes in coverage of maternal, newborn, and child survival interventions [5052]. Equity analyses have been conducted across various themes including maternal health [53, 54], immunization coverage [55], and child mortality [56]. A recent equity analysis on contracting mechanisms in Afghanistan recommended linking equity goals to performance bonus provided to service providers as an effective strategy for reducing the inequities [14].…”
Section: Discussionmentioning
confidence: 99%
“…The Countdown to 2015 Equity Analysis Group has resulted in several equity trend analyses of countries in changes in coverage of maternal, newborn, and child survival interventions [5052]. Equity analyses have been conducted across various themes including maternal health [53, 54], immunization coverage [55], and child mortality [56]. A recent equity analysis on contracting mechanisms in Afghanistan recommended linking equity goals to performance bonus provided to service providers as an effective strategy for reducing the inequities [14].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the relative scarcity of neonatal mortality, one-year death estimates were not adequately precise, 5 and could not ensure enough births to reduce effects of sampling error. 27,28 Hence, survival status of neonates was investigated during a 5-year observation period before the surveys in 2000 and 2010.…”
Section: Methodsmentioning
confidence: 99%
“…Olson et al found a relationship between inequality and infant mortality rate in the US, highlighting the importance of the first 1,000 days of life and their effects on adult health (Olson, Diekema et al 2010). In the Philippines, Kraft et al showed wealth equitymarkers were evident in relation to child mortality, and recent wealth-related inequalities were found to be strongly associated with many social factors (Kraft, Nguyen et al 2013). Another study in Ghana showed a strong association between childhood under-nutrition and inequality (Hong 2007).…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%